A Study of Skin-to-Skin Care During Cesarean Birth: A Mother's Experience - Bertrand, Kristen Marie (J Perinat Educ, 2020)
This study explores the experience of women who have had skin-to-skin care during cesarean birth by using a qualitative, phenomenology-based approach. Interview questions were developed and aimed to understand the common meaning of this experience by learning about women's prior concerns and expectations of skin-to-skin care during cesarean birth, and how these experiences were realized during the intervention. A purposive sample (N = 13) was recruited through social media. Participants had skin-to-skin care, post-cesarean birth, in the last 10 years and were interviewed via Facebook Messenger video chat. The themes that emerged revealed the importance these women placed on their skin-to-skin care experience. The results of this study reinforce the importance of advocating for and implementing skin-to-skin care during cesarean birth whenever possible.